Some pyrazoles derivatives: Potent carbonic anhydrase, ??glycosidase, and cholinesterase enzymes inhibitors - Turkan, Fikret; Cetin, Adnan; Taslimi, Parham; Gülçin, İlhami; Taslimi, Parham (Wiley, 2018)
A series of substituteed pyrazol-4-yl-diazene derivatives were found to be effective inhibitors against -glycosidase, cytosolic carbonic anhydrase I and II isoforms (hCA I and II), butyrylcholinesterase (BChE), and acetylcholinesterase (AChE) with K-i values in the range of 33.72 +/- 7.93 to 90.56 +/- 27.52nM for -glycosidase, 1.06 +/- 0.16 to 9.83 +/- 0.74nM for hCA I, 0.68 +/- 0.12 to 7.16 +/- 1.14nM for hCA II, 44.66 +/- 10.06 to 78.34 +/- 17.83nM for AChE, and 50.36 +/- 13.88 to 88.36 +/- 20.03nM for BChE, respectively. Recently, inhibition of these metabolic enzymes has been considered as a promising factor for pharmacologic intervention in a diversity of disturbances, such as diabetes, glaucoma, obesity, epilepsy, cancer, and neurodegenerative diseases.
Keywords: Acetylcholinesterase; Butyrylcholinesterase; Carbonic anhydrase; Enzyme inhibition; Substituted pyrazol-4-yl-diazene